Peran Humas Universitas Boyolali Dalam Upaya Meningkatkan Kerjasama Multinasional: Studi Deskriptif Penggunaan Teori Excellent Public Relations oleh Grunig - Anisa, Silvina Nur; Hartini, Sri; Setiawan, Topan; Hartini , Sri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
UBY Public Relations has had an extraordinary role in improving the image and multinational cooperation at UBY in the last 3 years. The aim of this research is to describe the role of UBY Public Relations in efforts to increase multinational cooperation. This research was studied using the Excellent Public Relations theory by Grunig. Data collection techniques were carried out using in depht interview, observation, and documentation. The research result show that: a) Public Relations is involved in all activities related to cooperation; b) Public Relations uses social media to disseminate information; c) Public Relations as a center for information related to cooperation; d) Public Relations empowers its team through jobdesk division; e) Public Relations acts as a communicator; f) Public Relations carries out two-way communication; g) Public Relations provides internal opportunities to provide criticism and input regarding Public Relations performance; h) Public Relations prevents acts of discrimination within the institution.